Epistemological-Motivational Bases of Literary Non-Fiction Genre as Factors Determining The Linguistic Structure of Text - Galstyan, Ashot (Տիգրան Մեծ)
This article dwells on epistemological-motivational aspects of the literary non-fiction genre. The general features of memoir literature are examined form the point of view of their epistemological and cognitive aspects. The cognitive and informational specificities of non-fictional narratives are also considered.
Keywords: Epistemology